Biochar Properties Influencing Greenhouse Gas Emissions in Tropical Soils Differing in Texture and Mineralogy. Issue 5 (1st September 2016) - Butnan, Somchai; Deenik, Jonathan L.; Toomsan, Banyong; Antal, Michael J.; Vityakon, Patma
Abstract : The ability of biochar applications to alter greenhouse gases (GHGs) (CO2, CH4, and N2 O) has been attracting research interest. However, inconsistent published results necessitate further exploration of potential influencing factors, including biochar properties, biochar rates, soil textures and mineralogy, and their interactions. Two short‐term laboratory incubations were conducted to evaluate the effects of different biochars: a biochar with low ash (2.4%) and high–volatile matter (VM) (35.8%) contents produced under low‐temperature (350°C) traditional kiln and a biochar with high ash (3.9%) and low‐VM (14.7%) contents produced with a high‐temperature (800°C) Flash Carbonization reactor and different biochar rates (0, 2, and 4% w/w) on the GHG emissions in a loamy‐sand Ultisol and a silty‐clay‐loam Oxisol. In the coarse‐textured, low‐buffer Ultisol, cumulative CO2 and CH4 emissions increased with increasing VM content of biochars; however, CO2 emission sharply decreased at 83 μg VM g −1 soil. In the fine‐textured, high‐buffer Oxisol, there were significant positive effects of VM content on cumulative CO2 emission without suppression effects. Regarding cumulative N2 O emission, there were significant positive effects in the Mn‐rich Oxisol. Ash‐induced increases in soil pH had negative effects on all studied GHG emissions. Possible mechanisms include the roles biochar VM played as microbial substrates, a source of toxic compounds and complexing agents reducing the toxicity of soil aluminum and manganese, and the role of biochar ash in increasing soil pH affecting GHG emissions in these two contrasting soils. Core Ideas: Biochar's volatile matter and ash constituents affect soil emission of CO2, CH4, and N2 O. Biochar volatile matter raised CO2 emission up to a threshold in coarse‐textured, low‐buffer soil. Biochar volatile matter raised CO2 emission regardless of its content in fine‐textured, high‐buffer soil. Biochar ash decreased emissions of greenhouse gases regardless of soil texture. Al in Ultisol and Mn in Oxisol interacted with volatile matter and ash in influencing GHG emissions.